Prothrombin polymorphism A19911G, factor V HR2 haplotype A4070G, and plasminogen activator-inhibitor-1 polymorphism 4G/5G and the risk of retinal vein occlusion. (3rd September 2017) - Kuhli-Hattenbach, Claudia; Hellstern, Peter; Nägler, Dorit Karin; Kohnen, Thomas; Hattenbach, Lars-Olof
ABSTRACT: Background : Thus far, no data has become available to evaluate systematically the prevalences of prothrombin polymorphism A19911G (PT A19911G), factor V HR2 haplotype A4070G (FV A4070G), or plasminogen activator-inhibitor-1 polymorphism 4G/5G (PAI-1 4G/5G) in patients who develop retinal vein occlusion (RVO) without cardiovascular risk factors. Materials and methods : We retrospectively evaluated comprehensive thrombophilia data from 42 preselected RVO patients without cardiovascular risk factors. The prevalences of different gene mutations and polymorphisms including factor V Leiden mutation G1691A (FVL), FV A4070G, prothrombin mutation G20210A, PT A19911G, and PAI-1 4G/5G were compared with 241 healthy controls matched for age and sex. Results : A total of 20 patients (47.7%) were found to carry thrombophilic gene polymorphisms including FVL, FV A4070G, and homozygous PT A19911G compared with 72 of 241 controls (29.9%; p = 0.03). Subgroup analysis of patients with a significant personal or family history of thromboembolism revealed a high prevalence of FVL, FV A4070G, and homozygous PT A19911G ( p = 0.005). FV A4070G was found to be significantly associated with at least two other heterozygous or one homozygous gene polymorphisms ( p = 0.02). Multivariate analysis revealed the presence of FVL ( p = 0.0017) and homozygous PT A19911G ( p = 0.03) polymorphism as independent risk factors for the development of RVO. Conclusions : Our results indicate that in selected RVO patients screening for thrombophilic gene polymorphisms including FVL, FV A4070G and homozygous PT G19911A may be helpful in a high percentage of cases. Our findings suggest that hereditary thrombophilia associated with RVO is more likely to be multigenic than caused by any single risk factor.